Master’s final projects as an approach to sustainable development of local communities: Experiences from the electrical engineering program at Universidad Politecnica Salesiana Guayaquil - Reyes-Lopez, Christopher Ruben; Jaime-Carriel, José Roberto; Cortez-Saravia, David Mateo (LACCEI, 2024)
Rural areas in developing countries often hold an abundance of natural supplies; most of these resources are not appropriately exploited, at least not to support the community's progress and its people. The Salesian Polytechnic University of Ecuador (Universidad Politecnica Salesiana de Ecuador - UPS) has always been involved in funding and executing short and long-term projects of such a diverse nature for the assistance to less-favored communities. Students from the master's program in electrical engineering, specifically at the branch located in Guayaquil, have been proposed to make their final projects on topics related to renewable energies, and smart grids, which may be employed to help small rural populations. In this context, this manuscript allows to understand the importance of carrying out a variety of master’s final projects on topics of power and energy engineering to boost the sustainable development of underserved localities, especially in rural areas. After the implementation and simulation of the projects under study, the outcome of this theoretical contribution makes it possible to recognize that universities are a key factor in promoting the growth of local economies and people’s lives in rural communities, as mentioned by interviewees in remarkable testimonials.